Pengembangan E-Booklet Tipe-Tipe Stomata Tumbuhan Famili Apocynaceae di Lingkungan Universitas Lambung Mangkurat Banjarmasin Sebagai Bahan Ajar Anatomi Tumbuhan - Azizah, Aprisa; Amintarti, Sri; Widiyastuti, Dewi Amelia (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Plants from the Apocynaceae family are commonly found in the environment of Lambung Mangkurat University, Banjarmasin, and can be utilized as learning materials, particularly in studying the sub-concept of stomata types. Providing appropriate learning resources and teaching materials that align with advancements in science and technology can enhance students’ learning motivation and engagement. One effective approach is the use of digital teaching materials such as electronic booklets (e-booklets). This study aims to describe the quality of the developed e-booklet based on suitability, feasibility, and readability tests. This research employed a development method using the 4D model (Define, Design, Develop, and Disseminate) proposed by Thiagarajan et al. (1974), conducted up to the dissemination stage in a limited and simplified manner. The subjects of the research and e-booklet evaluation consisted of two lecturers and eight students who had completed the Plant Anatomy course. The results showed that the suitability test obtained an average score of 4.79 (very suitable), the feasibility test obtained an average score of 4.75 (very feasible), and the readability test obtained an average score of 4.68 (very good). These findings indicate that the developed e-booklet is highly appropriate, feasible, and readable for use as a digital learning material in plant anatomy learning.